‘How the guineas shone as they came pouring out of the dark leather mouths!’: Shades of Gold in George Eliot’s Silas Marner (1861) - Marie-Laure Massei-Chamayou (Cahiers Victoriens et Edouardiens)
Far from the common representation of money in Victorian literature, with its many references to the expanding world of finance, credit and speculation, George Eliot’s Silas Marner (1861) depicts money mainly as gold coins, at the crossroads between realism and symbolism, the profane and the sacred. In this novella, gold is not merely the main dramatic thread that connects the parallel stories of Silas, Eppie and the Cass family, it also echoes mythical and Biblical narratives, such as the Book of Job, thereby lending itself to multiple interpretations: gold is, in turn, synonymous with a transgressive passion, an impure light or tainted matter which, as such, enables Silas’s successive transmutation, transformation and transfiguration, thereby partaking of the hero’s complex alchemical initiation and spiritual quest. At the end, the recovery of the stolen gold coins both leads to the emergence of the truth and works as a sign of divine reward for Silas’s spiritual progress. Such weaving of the multi-layered theme of gold into the narrative definitely gives birth to an effective poetics which may address several planes of consciousness.